2019
DOI: 10.15171/jhp.2019.26
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity studies of Acacia nilotica (L.): A review of the published scientific literature

Abstract: Introduction: Acacia nilotica is a valuable plant with medicinal properties that increasinglyincites the curiosity of many researchers. Its pharmacological properties are reported in manystudies, but the fact remains that the plant can be just as toxic as any modern pharmaceuticaldrug. It is very important to dispose sufficient knowledge on what are reported concerning itstoxicity profile. This review is aimed to provide comprehensive summary (all-in-one) of whathave been reported about the toxicity of A. nilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…An acute toxicity study conducted by the method of Lorke 1983 revealed that BF ANP has a relative LD 50 of 565mg/kg. During that toxicity study, we reported in some groups symptoms such as increased diuresis; weight loss occurred during the 72 h observation period which correlates with a previous report by (Manzo et al, 2019). Several studies demonstrated that the acetic acid-induced writhing test model is suitable to evaluate the peripheral type of analgesic action of herbal and other drugs (Dhara et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…An acute toxicity study conducted by the method of Lorke 1983 revealed that BF ANP has a relative LD 50 of 565mg/kg. During that toxicity study, we reported in some groups symptoms such as increased diuresis; weight loss occurred during the 72 h observation period which correlates with a previous report by (Manzo et al, 2019). Several studies demonstrated that the acetic acid-induced writhing test model is suitable to evaluate the peripheral type of analgesic action of herbal and other drugs (Dhara et al, 2000).…”
Section: Discussionsupporting
confidence: 85%
“…The plant is the best source of bioactive substances such as gallic acid, ellagic acid, isoquercetin, leucocyanidin, kaempferol-7-diglucoside, naringenin-7-O-β-D-(60-Ogalloyl) glucopyranoside, rutin, apigenin-6,8-bisC-glucopyranoside, m-catechol and their derivatives, as well as galloylated derivatives of (+)-catechin and (+)-gallocatechin (Malan, 1991;Singh et al, 2008;Maldini et al, 2011). Particularly, in our previous research work, we found the pods of the plant to be very rich in tannins and saponins (Manzo et al, 2019). Since the pods of Acacia nilotica are under intensive use by the community, the present study aimed to investigate the cytotoxicity effect of various organic extracts of the pods.…”
Section: Introductionmentioning
confidence: 71%
“…However, in vivo acute toxicity studies may be necessary to establish the safety level of the extract. Few studies conducted elsewhere have also studied the cytotoxicity effects of A. nilotica extracts against different mammalian cell lines (Kalaivani et al, 2011;Rasool et al, 2013;Manzo et al 2019). Van den Bout-van den Beukelet al (2008) reported highest cytotoxicity effects of the stem extracts of A. nilotica against Hep-G2 and HeLa human cell lines used as model.…”
Section: Discussionmentioning
confidence: 99%